Zonarol, a sesquiterpene from the brown algae Dictyopteris undulata, provides neuroprotection by activating the Nrf2/ARE pathway - Shimizu, Hiroya (Biochem Biophys Res Commun, 2015)
Seaweed-origin electrophilic compounds are proposed as a class of neuroprotective compounds that provide neuroprotection through activation of the Nrf2/ARE pathway. Electrophilic hydroquinones are of particular interest due to their ability to become electrophilic quinones upon auto-oxidation. Although many marine plants produce a variety of electrophilic compounds, the detailed mechanism of action of these compounds remain unknown. Here, we focused on the neuroprotective effects of zonarol (ZO), a para-hydroquinone-type pro-electrophilic compound from the brown algae Dictyopteris undulata. We show that ZO activates the Nrf2/ARE pathway, induces phase-2 enzymes, and protects neuronal cells from oxidative stress. ZO is the first example of a neuroprotective pro-electrophilic compound obtained from brown algae.